The poems entitled "(anhelo)". A structural trace of Dante in the book "De la intemperie" by José Luis Puerto - Godoy Gómez, Luis Miguel (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
This work analyzes the symbolic and personal reworking made by José Luis Puerto in his book De la intemperie of the structure used by Dante in his Divina comedia by distributing four thematic blocks that have the same number of poems and that end with one that repeats the same title, "(anhelo)". Being a resource that structures the entire work, a study of it is also provided.
Keywords: José Luis Puerto; Dante; Structure